Proteomics profile of Hanseniaspora uvarum enhanced with trehalose involved in the biocontrol efficacy of grape berry. (15th February 2019) - Apaliya, Maurice Tibiru; Yang, Qiya; Zhang, Hongyin; Zheng, Xiangfeng; Zhao, Lina; Zhang, Xiaoyun; Kwaw, Emmanuel; Tchabo, William
Highlights: Defense-related proteins of H. uvarum were up-regulated by trehalose treatment. Stilbene synthase of grapes was up-regulated by trehalose treated H. uvarum . Defense enzymes of grapes were activated by H. uvarum Y3. Abstract: This present study tested the extent to which 2% w/v trehalose enhanced the proteins expression profile of Hanseniaspora uvarum Y3. Furthermore, it explored the relative gene expression of stilbene synthase ( StSy ), one of the vital defense-related genes found in the skin of grapes. The proteomics profile revealed that 29 proteins were differentially expressed out of which 26 were significantly up-regulated and 3 were download-regulated. The pathogenesis related (PR) and other protein spots were visible at 97.4 kDa and 14.4 kDa. Peroxiredoxin TSA1 and superoxide dismutase were the main proteins involved in defense response and both proteins were significantly up-regulated. The carbohydrate and energy metabolism proteins were also significantly up-regulated. The results revealed that the treatments were associated with substantial increase in peroxidase activity compared to the control. StSy relative gene expression level was observed to increase by 2.5-fold in grapes treated with the pre-enhanced H. uvarum compared to the control.